A comprehensive literature review on spare parts logistics management in the maritime industry - Maria Mouschoutzi; Stavros T. Ponis (Asian Journal of Shipping and Logistics (AJSL), 2022)
Supply chain and logistics management for spare parts is of key importance in the maritime industry, in order to ensure high availability and reliability of assets, while keeping operating costs in acceptable levels. Supply chain and logistics operations for spare parts incorporate high complexity, uncertainty and costs, due to special characteristics of the maritime sector, as for instance moving assets, globally scattered points of supply and demand, strict time windows and multi-actor setting. Typically, the asset owner purchases spare parts for their vessel from a foreign supplier, and consolidates them in a regional warehouse. Subsequently, these spare parts are shipped to a port using various means of transport such as air freight, sea freight or road freight. Finally, once the vessel calls at subject port, the spare parts are delivered and used on board for maintenance activities. For repairable items, the reverse logistics process also does exist; a spare part is offloaded from a vessel, repaired and then re-delivered on board. Efficiently handling such a logistics network constitutes a great challenge, nevertheless, this topic has received little attention in the literature and a systematic review is currently missing. In this paper, the authors attempt to address this research gap by performing a systematic literature review on spare parts supply chain and logistics management in the maritime sector. To achieve this objective, after applying the defined inclusion and exclusion criteria on the initial search results, a set of (30) eligible papers, participating in the review, has been identified. These selected papers are illustrated and discussed in detail, with the purpose of addressing the research questions initially set by the authors. Fundamentally, this study aims to describe the current state of the art in the subject area, identify existing challenges and trends, and finally provide suggestions on future research. We aspire that the results of this review can be used as the foundation for future research on spare parts supply chain management in the maritime sector.
Keywords: 650; Logistics; Maintenance; Maritime; Shipping; Spare parts; Supply chain